Literature Review: The Iceberg Phenomenon in Hyperthyroidism and Mental Disorders - Priskila, Loury; Dinata, Fenita Renny; Danuartha, Made Anom; Tamma, Haryadi Aristo; Herlambang, Yosafat Reza (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Background: Elevated thyroid hormone levels have a high prevalence this year. It has a long-term impact on the cognitive and productivity of sufferers, leading to a decrease in the quality of life of individuals and an increase in social and economic burden. Previous studies have shown a direct link between hyperthyroidism and mental disorders, but the impact on cognitive and emotional functioning still needs to be clarified. Early detection and management are the main challenges in preventing and treating this condition. Methods: Our study was a literature review of medical journal for the last 10 years through NCBI, Google Scholar, Clinicalkey, Semantic Scholar, Sciencedirect, and Springer. Result: Hyperthyroidism caused by dysregulation of the Hypothalamic-Pituitary-Thyroid axis that disrupts the balance of triiodothyronine and thyroxine hormones, leading to emotional and cognitive impairment. The brain and thyroid tissue are also affected by the FDPS, PPIL3, MMAB, and ALDH2 genes, which are characterized by significant expression in areas of brain function that are involved in cognitive, emotional, and social behaviour. Conclusion: A multidisciplinary approach, including pharmacological therapy, cognitive therapy, and community education, is an important step in reducing the impact of hyperthyroidism on mental health as well as social and economic aspects.